Knowledge, Attitude, And Practice of Infection Control Measurement During Covid-19 Pandemic Among Dental Assistant in Hafar Al-Batin, Saudi Arabia - Aldhafeeri, Maha Jubayr; Al-Mutairi, Ali Falah; Aldhafeeri, Dalail Batah A; Alsuhali, Seta Mohammed; Aldhafeeri, Nawal Batah A; Alzahrani, Khames T. (International Journal of Innovative Research in Medical Science, 2022)
Background: Health care workers, including dentists, dental assistants are at high risk at acquiring and transmitting infection within their work environment due to close contact with patients and the instruments they use that spread droplets, aerosols of blood and saliva. The main objective of this study is to assess knowledge and awareness about infection control measurement during covid-19 pandemic among dental assistant. Methods: A cross-sectional online survey among dental assistant in Hafar Al-Batin, KSA. An online questionnaire was employed to collect data. The Statistical Package for Social Sciences (SPSS) version 26 was used for data management. We assessed COVID-19 knowledge, knowledge about current guidelines for infection control, and adherence to them. Results: The study included 398 participants. Our study showed an overall high adherence level to COVID-19 infection control measures and recommendations as the average practice score was 32.2 ± 6.7 out of 39. There was a significant association between practice score and gender (p=0.019), knowing about COVID-19 (p=0.006), source of COVID-19 information (p=0.000), and having completed an educational course on COVID-19 (p=0.002). Conclusion: Higher infection control practice scores were evident among males, those who knew of COVID-19, those whose source of knowledge was MOH, and those completed an educational course on COVID-19. We recommend further educational activities in order to improve infection control practice and adherence to guidelines.